IMPLEMENTATION OF INTERDISCIPLINARY INTEGRATION IN PROFESSIONAL-ORIENTED EDUCATION OF FUTURE TEACHERS - Пащенко, М.І.; Черненко, Любовь (Modern engineering and innovative technologies, 2022)
The article defines the purpose of realization of interdisciplinary level of integration at preparation of the future teacher. The directions, criteria are analyzed: the task of the master class, which promotes the study and implementation of vertical in